Elogio de la diversidad. Acerca del manifiesto de la creolidad de Jean Bernabé, Raphaël Confiant y Patrick Chamoiseau (Altre Modernità, 2011)
From reading In praise of Creoleness (1988) by Jean Bernabé, Raphaël Confiant y Patrick Chamoiseau, this paper propose to approach to the need of establishing a Creole literature in the Caribbean islands. With this objective, it considers the relationships that set the group of Creoleness with Negritude and the Caribbeanness, especially through its main exponents: Aimé Césaire and Édouard Glissant. It covers the main points of the manifesto of the Creoleness paying special attention to the features that takes "diversity”, as this concept becomes the basis on which the authors are supported to enhance the Creole culture. Thus, you can see in the text a shift in modes of perception of others that defines not only a change in terminology but also a change of perspective: the world Creole ceases to be exotic to start to be diverse.